Glaucoma-like optic neuropathy in patients with intracranial tumours - Qu, Yuanzhen; Wang, Ya Xing; Xu, Liang; Zhang, Liwei; Zhang, Junting; Zhang, Jianguo; Wang, Lina; Yang, Liu; Yang, Anchao; Wang, Jian; Jonas, Jost B. (Acta ophthalmologica, 2011)
PURPOSE: To examine frequency and associated factors of glaucoma-like appearance of the optic nerve head in patients with intrasellar, suprasellar or parasellar tumours. - METHODS: This retrospective clinical observational study included patients who were consecutively treated for intrasellar tumours (n = 143), suprasellar tumours (n = 321), parasellar tumours (n = 36) or retrosellar tumour (n = 1), and all of whom had undergone fundus photography and full-threshold visual field examination. The tumour spectrum included 336 pituitary gland tumours, 32 meningiomas, 89 craniopharyngiomas, 9 chiasmal gliomas and 35 other types of tumours or lesions. An age-matched control group was formed from the population-based Beijing Eye Study. Using fundus photographs and visual field examinations, glaucoma was defined by a neuroretinal rim shape not following the ISNT rule (Disc glaucoma group) and by an abnormal rim shape plus glaucoma-like visual field defects (Field glaucoma group). Type and size of the tumours were assessed on neuroradiological images. - RESULTS: Five-hundred and one patients fulfilled the inclusion criteria. Disc glaucoma and Field glaucoma were detected significantly more frequently in the study population [34 (6.8%) patients and 31 (6.3%) patients, respectively] than in the population-based control group of the same ethnicity (1.3% ± 0.5%; p < 0.001). In multivariate analysis, presence of Disc glaucoma [odds ratio (OR) = 2.64; p = 0.016] and presence of Field glaucoma (OR = 3.01; p = 0.027) were significantly associated with tumour location [suprasellar > parasellar > intrasellar]. The same held true for tumour width (OR = 1.08; p = 0.002; and OR = 1.08; p = 0.003, respectively). - CONCLUSIONS: Large perisellar tumours were associated with a glaucoma-like appearance of the optic nerve head in eyes. It may diagnostically and pathogenetically be of importance.
Gesehen am 23.01.2023